2021
DOI: 10.1016/j.annemergmed.2021.04.027
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Four Frequently Used Frailty Instruments for the Prediction of Adverse Health Outcomes Among Older Adults at Two Dutch Emergency Departments: Findings of the AmsterGEM Study

Abstract: Older adults presenting to the emergency department (ED) are at high risk of adverse health outcomes. This study aimed to evaluate the accuracy of 4 frequently used screening instruments for the prediction of adverse health outcomes among older adults in the ED.Methods: This was a prospective cohort study in patients 70 years of age presenting to the ED in 2 hospitals in the Netherlands. Screening instruments included the acutely presenting older patient screening program (APOP) (providing 2 risk scores-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The results of this study show that successful implementation of frailty screening tools in the ED does not depend on the type of screener because all frailty screening tools were easy, quick to perform and generally well accepted by healthcare professionals working in the ED. This is similar to the results of prior studies as shown in the review by van Dam et al [9]. However, participants did mention barriers like workload and lack of clear benefits in using a screening tool.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study show that successful implementation of frailty screening tools in the ED does not depend on the type of screener because all frailty screening tools were easy, quick to perform and generally well accepted by healthcare professionals working in the ED. This is similar to the results of prior studies as shown in the review by van Dam et al [9]. However, participants did mention barriers like workload and lack of clear benefits in using a screening tool.…”
supporting
confidence: 87%
“…This is similar to the results of prior studies as shown in the review by van Dam et al . [9]. However, participants did mention barriers like workload and lack of clear benefits in using a screening tool.…”
mentioning
confidence: 99%
“…This prospective cohort study—the Amsterdam Geriatric Emergency Medicine study (AmsterGEM) [ 14 ]—was conducted at the ED of two Dutch hospitals: tertiary academic hospital Amsterdam UMC location VUmc in Amsterdam and the general community hospital Amstelland in Amstelveen. Data were collected on a daily basis from November 2017 to June 2018, mostly during office hours, and during a limited number of evenings and weekend days.…”
Section: Methodsmentioning
confidence: 99%
“…For the AmsterGEM study [ 14 ], research students screened every patient aged ≥ 70 years attending the ED for eligibility, regardless of the reason for presentation and/or specialty they presented for. Exclusion criteria were patients labeled as high urgency (according to the Manchester Triage System—code red [ 15 ]), language barrier, unknown number of prescriptions, limited length of stay at the ED, or inability to give informed consent (for example due to altered mental status in the absence of a caregiver who could provide informed consent by proxy).…”
Section: Methodsmentioning
confidence: 99%
“…Screens performed in the ED for health‐related social needs, substance abuse disorders, or behavioral health problems have led to successful intervention to address identified patient problems 23–25 . Previous studies of frailty scores performed in the ED found that individuals identified as severely frail had increased risk of repeat ED visits, admission, and mortality 26–28 . To date there have been no published studies on the application of frailty scores within the VA ED population.…”
Section: Introductionmentioning
confidence: 99%